"By means of tigers": Jaguars as Agents of Conversion in Jesuit Mission Records of Paraguay and the Moxos, 1600–1768. Issue 4 (13th November 2015) - Vélez, Karin
Abstract : In the mid-1600s, the Jesuit Antonio Ruiz de Montoya reported that man-eating jaguars were helping to convert Guaraní Indians to Catholicism. This article tests his claim by aggregating multiple mentions of jaguars found in the accounts and letters of Jesuit missionaries in the reductions of Paraguay and the Moxos from the seventeenth and early eighteenth centuries, including the writing of Jesuits Antonio Ruiz de Montoya, François-Xavier Eder, Alonso Messia, and Martín Dobrizhoffer. Cumulatively, their predator sightings and references suggest that, indeed, the actions of real jaguars were transforming local religious beliefs. The presence of jaguars in Jesuit records also reveals the complexity of missionary and indigenous attitudes towards animals. Jesuits often associated jaguars with pre-Christian jaguar-shaman rituals, but also considered them to be divine instruments. Indigenous peoples sometimes preserved older practices, but also occasionally took real jaguars as an impetus to convert to Christianity. Both Jesuits and indigenous peoples reacted to jaguar incursions with violence as well as spiritual reflection. Most importantly, the prominence of active jaguars on this contested religious frontier suggests that animals should be viewed as more than symbols in Christian history. Jesuit records indicate that jaguars were key third players in zones where Europeans and indigenous populations met.